Effects of different loads applied on a newly-designed container for oyster grow-out culture using finite element analysis - Arifin, Arzul; Yusuff, Mohd Asri; Wong Wai Sin, Nur Leena; Zakaria, Kamarul Arifin (Praise Worthy Prize, 2023)
In general, oyster culture in Malaysia relies on traditional methods. This study focused on the grow-out stage, particularly on the containers used to hold the oysters during this phase. The existing containers are in the form of modified plastic baskets, which are not fully covered for protection against predators, with only a single layer production. The newly-designed container consists of multilevel stacks, with a door that can be closed and locked. A mechanical simulation analysis was conducted to ensure the structure could hold the intended recommended maximum working loads of 25 kg. A series of different loads and water current speeds were applied to the structure of the new oyster container. Results of the analysis conducted showed the stress value increased when the loads increased, for all panels, the highest being 6.66 MPa, under a load of 50 kg and water current speed of 0.6 m/s. However, the all-stress values obtained for all panels were well below the yield strength of the polypropylene material used. Thus, the new oyster container structure was proven to be safe and sound under the different applied loads, making it reliable to operate.